Profitability vs Poverty alleviation: has banking logic influences Islamic microfinance institutions? - Luqyan Tamanni; Mohd Hairul Azrin Haji Besar (Emerald Publishing Limited, 2019)
The purpose of this paper is to shed some lights on the process of mission drifting or abandoning poverty objective by Islamic microfinance institutions (IMFs). The paper investigates whether the extensive use of banking logic changes IMFs, from focusing on both development and financial objectives to only considering sustainability as their primary mission.This paper adopts mixed methods by analyzing 7,200 microfinance data from Microfinance Exchange Market and reviewing annual reports and websites of 25 IMFs to examine their vision and mission statements and other related information.The finding shows Islamic microfinance has not changed, despite increasing adoption of financial or banking performance measures. However, size and age of the institutions may affect the outcome in the future. The authors find that smaller microfinance institutions maintain genuine objective to serve the poor, as the grow larger they would be more inclined toward sustainability objectives.The research is limited on the sample size as data on Islamic microfinance globally is limited. However, the paper looked at the global data rather than local data to compensate for this limitation. Future study would be further taking the study through qualitative methods to support the study.This paper aims to shed some lights on the process of mission drifting or abandoning poverty objective by IMFIs. The paper investigates how has the extensive use of financing logic has changed IMFIs from focusing on both development and financial objectives to only considering sustainability as their primary mission. Arun and Hulme (2009) argued that the interaction of multiple logic within microfinance institutions, i.e. financial vs social, could pose some serious management dilemmas within microfinance institutions. Further, commercialization puts pressure on the field staffs to achieve financial targets and often neglect their poverty outreach mission to the poor. The well-known crisis in Andhra Pradesh, India where clients of microfinance institutions committed suicide after being shamed by field officers who tried to collect payments of loans (Mader, 2013; Taylor, 2011), provides a powerful case of the impact of financialization to microfinance clients.